Selected principles, elements and experiences of privatisation in Germany - Karl Fasbender (Hamburg Institute of International Economics (HWWA), 2004)
In most states with market oriented economic systems privatisation plays an important role in the political discussion, mainly due to the fundamental problem of all economic systems, which is scarcity of available resources. The responsible politicians try to improve the allocation of scarce resources and to increase the financial possibilities for needed development investments by creating an adequate macroeconomic framework and a business-friendly environment. Within the scope of these efforts the production of goods and commercial services by state-owned enterprises only plays a very limited role. The state would be best advised to leave these functions to the, in this regard, more efficient private sector. The public sector should concentrate its respective efforts only on the production of so-called Public Goods and, for political reasons, eventually on some sub-sectors, which are essential for the security of the country. Nearly all market economies and especially states which are in the transitional process from more centrally administered to market oriented economic systems, have room for manoeuvre towards privatisation of state-owned enterprises. Privatisation facilitate the improvement of factor allocation and the reduction of budget constraints, not only by the way of sales revenues but also by creating a broader tax-base, decreasing the need to provide subsidies and, last but not least, mobilising private resources for the aimed development-process. This is also true for the Republic of India as well as for the Federal Republic of Germany. [...] This Report gives an overview of selected principles, elements and experiences of privatisation in Germany, with special reference to the new Federal States in East Germany and under consideration of selected aspects in neighbouring countries. The intention is not to present a complete abstract, but to provide a discussion basis for identifying starting points for a future dialogue about lessons learnt.
Keywords: 330